The relationship between lecturers’ teaching style and students’ academic engagement - Shaari, Abdull Sukor; Mohd Yusoff, Nurahimah; Mohd Ghazali, Mohd Izam; Osman, Rafisah; Mohd Dzahir, Nur Fatirah (Elsevier Ltd., 2014)
This study aimed to identify the relationship between lecturers’ teaching style and students’ academic engagement in a university in Malaysia The study was conducted using a survey through questionnaires distributed to 266 students.Types of teaching styles used are in accordance with the teaching style of Grasha (1996).In order to determine the dimensions of the lecturers’ teaching style and students’ engagement level in academic, the descriptive statistics based on percentage, mean and standard deviation were used.As for the lecturers’ teaching styles, majority of the lecturers use personal model followed by expert style, while delegator style gets the lowest mean.Majority of the respondents were found to have involved in academic engagement.The results also show that there is a significant but moderate relationship between lecturers’ teaching style with the students’ academic engagement.